Types of Accidents in Nineveh Governorate / Iraq - Ibrahim Al-Sammak, Najlaa (International Journal of Psychosocial Rehabilitation, 2020)
Background: Accidents are one of the leading causes of morbidity and mortality all over the world. They affect usually young people as they are more prone to the external environmental hazards leading to loss of the current and future working force in the community. Thus it is important to identify accidents’ types and their victims in order to plan and apply the required interventions that can prevent or reduce some of these avoidable life threatening problems. Objective: Identify the main types of accidents in Nineveh Governorate during the period 2008-2009 and 2018- 2019. Methods: A biometric study design was used in this research in which mortality data related to accidents for the whole governorate were utilized and formulated into meaningful tables. These data were obtained from the Forensic Medicine Department for the years 2008, 2009, 2018, and 2019. Several rates and proportions were measured to identify and rank various forms of accidents and their related data. Results: This study demonstrated that explosions, shooting, and road traffic accidents were the main types of accidents in the governorate throughout the study period. They mostly affected young and male population. Making a comparison between two periods (2008-2009) and (2018-2019) showed that most of accidents’ types were increasing by time except for slaughtering, shooting, and burns. Conclusion and Recommendation: Nineveh was strongly loaded by terrorism related mortality for many years particularly by explosions and shooting that harvesting hundreds of young population’s lives each year. So, it is important to focus attention to this governorate and its people who are greatly damaged by terrorism and violence.